Effect of dry fermented rumen liquor on productive indicators of replacement White Leghorn laying hens - Rodríguez, Bárbara; Savón, Lourdes; Elías, A.; Herrera, Magaly (Cuban Journal of Agricultural Science, 2022)
A total of 840 animals, from 1 to 126 days of age, randomly distributed into four experimental treatments, were used for evaluating the effect of including 0, 1, 2 and 3 % of dry fermented ruminal liquor in the diet on productive performance. Viability of hens was higher than 96 %, which shows that these treatments had no negative effects on health. Feed intake was not affected by the product. However, at 84 d, feed conversion (P=0.0003) and liveweight (P=0.0008) improved with respect to the group in which it was not included. From day 1 to 126, only differences were found between the 2% treatment and the untreated group for feed conversion (4.51 vs. 4.76, P=0.0245) and liveweight (1419 vs. 1349, P=0.0360). Mean liveweight of the batch, in each stage, had a coefficient of variation lower than 8, which corresponds to a uniformity superior to 90%, which indicates that it was good. No effect of treatment on ovary and oviduct development was found. Dry fermented ruminal liquor improved liveweight and feed conversion of replacement layers with high viability and uniformity. Results suggest the use of this product up to 3% in the diet of this poultry category. Keywords: poultry, rumen content, fermentation, additive